Radiocarbon chronology of Neolithic in the Lower Don and North-eastern Azov Sea - Andrey Tsybryi; Viktor Tsybryi; Ekaterina Dolbunova; Andrey Mazurkevich; Marianna Kulkova (Documenta Praehistorica, 2017)
So far, four different cultural-chronological groups of sites have been identified in the North-eastern Azov Sea and Lower Don River areas, including sites of the Rakushechny Yar culture, Matveev Kurgan culture, Donets culture, and sites of the Caspian-Ciscaucasian region. An analysis of all known dates, as well as the contexts and stratigraphies of the sites, allowed us to form a new perspective of the chronology of southern Russia, to revise the chronology of this region, and change the concept of unreliability of dates for this area.